2019
DOI: 10.3390/w11020217
|View full text |Cite
|
Sign up to set email alerts
|

Scale up of Microbial Fuel Cell Stack System for Residential Wastewater Treatment in Continuous Mode Operation

Abstract: The most important operational expense during wastewater treatment is electricity for pumping and aeration. Therefore, this work evaluated operational parameters and contaminant removal efficiency of a microbial fuel cell stack system (MFCSS) that uses no electricity. This system consists of (i) septic tank primary treatment, (ii) chamber for secondary treatment containing 18 MFCs, coupled to an energy-harvesting circuit (EHC) that stores the electrons produced by anaerobic respiration, and (iii) gravity-drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 46 publications
(66 reference statements)
1
10
0
Order By: Relevance
“…However, the high variability within the reactor between identical commercially made electrode cassettes may be a greater challenge for industry to accept, as it introduces uncertainty and therefore risk. This variability has been documented in other pilot studies [1,2,10,50,51], and it shows that some electrodes are operating far below their potential. Major application of this technology cannot occur without further investigation into this electrode variability and analysis of the biofilm formation process.…”
Section: Discussionsupporting
confidence: 64%
“…However, the high variability within the reactor between identical commercially made electrode cassettes may be a greater challenge for industry to accept, as it introduces uncertainty and therefore risk. This variability has been documented in other pilot studies [1,2,10,50,51], and it shows that some electrodes are operating far below their potential. Major application of this technology cannot occur without further investigation into this electrode variability and analysis of the biofilm formation process.…”
Section: Discussionsupporting
confidence: 64%
“…The feasibility of treating raw waste produced from a house of five inhabitants by MFC-based wastewater pilot plant with no external energy use was investigated in another study. The results were promising in terms of the quality of the treated effluent, which could successfully comply with the maximum national standards [49]. Additionally, it was shown that the temperature could strongly affect various variables, such as wastewater conductivity, activation energy, charge transfer rates, electrochemical reactions, etc.…”
Section: Microbial Fuel Cellsmentioning
confidence: 89%
“…Linares et al ( 2019) [94] reported that COD removal in several studies achieved ranges from 36% to 84%. It could be said that the results of this study are still on the normal performance of MFC research, even though the maximum COD removal could achieve up to 78%.…”
Section: Factors Affecting the Performancementioning
confidence: 99%